Características morfoanatômicas e nutricionais de Aspidosperma olivaceum Müll. Arg (Apocynaceae) em um gradiente de altitude de uma floresta estacional semidecidual montana - Nadalete, Bruna de Oliveira (2017)
The species Aspidosperma olivaceum Müll. Arg is popularly known as "guatambu", "peroba" or "peroba-branco", which occurs in the Atlantic Forest of Minas Gerais until Santa Catarina, Brazil. This study aimed to characterize the morphoanatomy and nutritional content of Aspidosperma olivaceum Müll. in a semideciduous seasonal forest in Minduri, Minas Gerais, Brazil, occurring along six altitudinal (1000m, 1100m, 1200m, 1300m, 1400m and 1500m) Analysis of the specific leaf area, scanning electron microscopy (SEM) and nutritional analysis of the leaf. For the morpho-anatomic variables with significant correlation with altitude, regression analyzes were performed. The nutritional analysis data were submitted to analysis of variance and the comparison of the means by the Scott-Knott test. It was observed that the altitude had a significant and positive correlation with the thickness of the palisade parenchyma, the leaf blade, the cuticle, and the xylem area. The specific leaf area also had a significant correlation with altitude, but negative. It was observed an elongation of the palisade parenchyma as well as a reduction of the intercellular spaces of the spongy parenchyma with the increase of the altitude. The cuticle and xylem area and outer portion of the phloem increased. The SEM showed a large amount of trichomes and papillae on the abaxial surface, these already described by several authors as characteristic of the genus. Among the analyzed macronutrients, N contents were lower in the 1400 and 1500 m levels, the K contents were higher only in the 1100 m altitude, and the Mg contents were lower at 1200 m altitude. Among the micronutrients analyzed, the Mn contents were lower only at the elevation of 11 00 m, while the Zn contents were reduced in all the elevations from 1100 m altitude. In general, the availability of nutrients in soils of regions of higher altitudes tends to be lower due to leaching processes, lower soil temperature or lower rate of microbial activity. The study evidenced that specific leaf area is the variable with greater plasticity, followed by palisade parenchymal thickness and cuticle thickness. The species presented high leaf plasticity in the altitudinal dimensions studied through adaptive anatomical characteristics. These characteristics seem to improve the absorption of CO2 at higher altitudes, while avoiding the loss of water by transpiration. This work promotes new anatomical studies with A. olivaceum in high altitude forests, since they are still little explored